2013
DOI: 10.1007/s11552-012-9487-0
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Outcomes of Revision Amputation Treatment for Fingertip Amputations

Abstract: Purpose The purpose of this study was to conduct a systematic review of outcomes of fingertip revision amputation for fingertip amputation injuries in the Englishlanguage literature to provide best evidence of functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…On average, the ROM of the DIP joint after reconstruction was 63°, which is within the normal range (60°-90°) and return-to-work time was 7 weeks, which is regarded as early recovery [37]. These outcomes were similar to the outcomes reported by Wang et al [36].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…On average, the ROM of the DIP joint after reconstruction was 63°, which is within the normal range (60°-90°) and return-to-work time was 7 weeks, which is regarded as early recovery [37]. These outcomes were similar to the outcomes reported by Wang et al [36].…”
Section: Discussionsupporting
confidence: 83%
“…Alagoz et al [7] (n = 14), Yazar et al [8] (n = 70), and Kayalar et al [9] (n = 6) reported excellent sensibility outcomes (static 2PD 6.5, 5.7, and 4.3 mm, respectively) using sensate flaps. The sensibility outcome was similar to that reported by Sebastin et al [35], and slightly weaker than the outcome reported by Wang et al [36]. On average, the ROM of the DIP joint after reconstruction was 63°, which is within the normal range (60°-90°) and return-to-work time was 7 weeks, which is regarded as early recovery [37].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Revision amputation is a simple and practical method. It can achieve almost normal sensibility and satisfactory motion [6]. However, it also has many disadvantages, such as frequent cold intolerance [7], painful neuroma formation [8], shortening of the ngers and poor appearance.…”
Section: Discussionmentioning
confidence: 99%